ANALYSIS OF THE IMPACT OF RISK AND WORKLOAD ON MOTIVATION AND IMPACT ON EMPLOYEE PERFORMANCE - Eti Rusmiati; Dikdik Harjadi; Lili Karmela Fitriani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the effect of risk and workload on employee motivation and performance, as well as analyze the influence of work motivation on employee performance. This research was conducted at El-Syifa Kuningan Hospital. The population in this study was all employees of El-Syifa Hospital. The sample consisted of 137 respondents who were taken using non-probabilty sampling techniques, namely saturated sampling. The analysis tool used in this study is Structural Equation Modelling (SEM) with the help of AMOS program. The results showed that work risk has no effect on motivation or performance, workload affects the motivation and performance of employees. Work motivation affects employee performance